Modifikasi Mesin Pengupas Kulit Pinang Kering - Fathir Alqodri; Ruzita Sumiati; Rakiman Rakiman; Yuli Yetri; Desmarita Leni (Politeknik Negeri Padang, 2021)
Due to the weaknesses of some existing areca peelers, some modifications were made. Modifications were made to the gear stripper, the addition of the inlet funnel, the gear stripper cover, and the exit funnel. The purpose of this modification of the design of the areca nut peeling machine is to make it easier for areca-producing farmers to peel their skin. Engine design specifications, using a 1/2 HP motor with a speed of 1500 rpm, 2-inch, and 10-inch pulleys, and a capacity of 5.16 kg/hour. The result of this modification is stated to be able to perform stripping with a large capacity. This machine is expected to be able to meet the needs of manual areca nut peelers to increase productivity.